Garrisoned minds women and armed conflict in South Asia - Murthy, Laxmi, 1962-; Varma, Mitu; Panos Institute, India (New Delhi Speaking Tiger, 2016)
Supported by PANOS South Asia and few other international bodies; a study.
Keywords: Women -- Crimes against -- South Asia; Women and war -- South Asia; Women -- South Asia -- Social conditions